A study of the teenage population in the Portibi subdistrict of the North Padang Lawas Regency - Nurhaslinda; Siregar, Ervina Mulia; Anggaraini, Popy (PT Inovasi Pratama Internasional, 2024)
The percentage of teenage pregnancies in Indonesia is 0.02% at the age of <15 years and 1.97% at the age of 15-19 years in Portibi sub-district, North Padang Lawas District. Adolescent mothers are known to have low exclusive breastfeeding coverage rates. The purpose of this study was to determine the factors that influence exclusive breastfeeding in adolescent mothers in Portibi sub-district, North Padang Lawas Regency. This study used a survey method with a cross-sectional design. The study population was teenage mothers who had babies aged 6-24 months in Portibi sub-district, North Padang Lawas Regency. Data collection using questionnaires. Bivariate analysis used chi square and fisher's exact test while multivariate analysis used logistic regression. The results showed 46.7% of teenage mothers provided exclusive breastfeeding. Bivariate analysis showed that pregnancy status (p=0.029), perceived birth experience (p=0.045), perceived breastfeeding (p=0.005), husband support (p=0.009), family support (p=0.000) were associated with exclusive breastfeeding, education level (p=0.143) and employment status (p=0.352) were not associated with exclusive breastfeeding. Multivariate analysis showed that family support (p=0.014; RP=7.637) and breastfeeding perception (p=0.015; RP=9.746) were associated with exclusive breastfeeding. Family support was the most dominant factor in exclusive breastfeeding among adolescent mothers. Adolescent mothers who received support from their family and had a positive perception of breastfeeding had a 72.7% probability of exclusive breastfeeding.